Kajian Perencanaan Energi Listrik di Wilayah Kabupaten Sorong Menggunakan Perangkat Lunak LEAP - Eric H. Tampubolon; Hans Tumaliang; Meita S. Rumbayan (Universitas Sam Ratulangi, 2014)
Abstract Act No. 30 Year 2009 on Electricity in Chapter VI mandate that local goverments must develop the General Plan of Regional Electricity. This study aims to predict the level of consumption (demand) of electricity in 2013 to 2020 per sector tariffs for Sorong regency. Additionally it also calculated the amount of electrical energy customers Sorong regency and elasticity. The data needed include PLN data about the number of customers and consumption of energy in each sector 2007-2012 period, Gross Domestic Product data (GDP) of Sorong regency, as well as some other data that support. Processing of the data to predict the level of consumption of electrical energy using software LEAP (Long-range Energy Alternatives Planning System). Demand is calculated based on the amount of activity and the amount of electrical energy consumption of electrical energy consumption per activity (energy intensity). In 2013 as the base year calculation. The results obtained from the electrical energy demand forecast in 2012-2030 showed a positive number that is increased from 2.5 MW to 38.1 MW. The rate of growth - average is 17,4% annually. This research expected to provide input for the local Goverment of Sorong District in the energy policy in particulary and regional development planning in general. Keyword : electricity, energy elasticity, energy intensity, LEAP Abstrak Undang – undang No. 30 Tahun 2009 tentang ketenagalistrikan dalam Bab VI pasal 7 mengamanatkan bahwa Pemerintah Daerah wajib menyusun Rencana Umum Ketenagalistrikan Daerah. Penelitian ini bertujuan untuk memprediksikan besarnya tingkat konsumsi (permintaan) energi listrik tahun 2013 hingga 2020 per sektor tarif untuk Kabupaten Sorong. Selain itu dihitung pula jumlah pelanggan energi listrik Kabupaten Sorong dan elastisitas. Data – data yang diperlukan antara lain data PLN tentang jumlah pelanggan dan konsumsi energinya di masing – masing sektor periode 2007-2012, data Produk Domestik Regional Bruto (PDRB) Kabupaten Sorong, serta beberapa data lainnya yang mendukung. Pengolahan data untuk memprediksi tingkat konsumsi energi listrik menggunakan perangkat lunak LEAP (Long-range Energy Alternatives Planning System). Permintaan dihitung berdasarkan besarnya aktivitas pemakaian energi listrik dan besarnya pemakaian energi listrik per aktivitas (intensitas energi). Tahun 2013 sebagai tahun dasar perhitungan. Hasil yang diperoleh dari prediksi permintaan energi listrik pada tahun 2013-2030 menunjukkan angka yang positif yaitu meningkat dari 2,5 MW menjadi 38,1 MW. Pertumbuhan rata – rata setiap tahunnya adalah 15,9 %. Dari penelitian ini dihasilkan gambaran dan masukan bagi Pemerintah Kabupaten Sorong dalam pengambilan kebijakan bidang energi pada khususnya dan perencanaan pembangunan kewilayahan pada umumnya.. Kata kunci :energi listrik, elastisitas energi, intensitas energi, LEAP